2020
DOI: 10.1080/21505594.2020.1770482
|View full text |Cite
|
Sign up to set email alerts
|

TMT-based quantitative proteomics analysis reveals the attenuated replication mechanism of Newcastle disease virus caused by nuclear localization signal mutation in viral matrix protein

Abstract: Ji (2020) TMT-based quantitative proteomics analysis reveals the attenuated replication mechanism of Newcastle disease virus caused by nuclear localization signal mutation in viral matrix protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 101 publications
(155 reference statements)
0
11
0
Order By: Relevance
“…Other studies reported that the VSV M protein directly inhibits host cell transcription by inactivating host RNA polymerases I and II [ 44 ] and interacts with nuclear pore complexes to impair nuclear export of cellular mRNAs, which indirectly leads to a decrease and an increase in host cell and virus gene transcription, respectively [ 45 47 ]. Recently, we revealed that nuclear localization of the NDV M protein possibly affected host cell transcription because transcription repressor activity-related differentially expressed (DE) genes were upregulated and transcriptional activator activity-related DE genes were downregulated [ 10 ], and the expression of most DE proteins related to “transcription” and “RNA processing and modification” was significantly decreased in NDV-infected cells early in infection when compared to that in cells infected with the mutant NDV harbouring M/NLS mutation [ 48 ]. More importantly, these upregulated or downregulated DE genes participated in regulating viral RNA synthesis and NDV replication [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported that the VSV M protein directly inhibits host cell transcription by inactivating host RNA polymerases I and II [ 44 ] and interacts with nuclear pore complexes to impair nuclear export of cellular mRNAs, which indirectly leads to a decrease and an increase in host cell and virus gene transcription, respectively [ 45 47 ]. Recently, we revealed that nuclear localization of the NDV M protein possibly affected host cell transcription because transcription repressor activity-related differentially expressed (DE) genes were upregulated and transcriptional activator activity-related DE genes were downregulated [ 10 ], and the expression of most DE proteins related to “transcription” and “RNA processing and modification” was significantly decreased in NDV-infected cells early in infection when compared to that in cells infected with the mutant NDV harbouring M/NLS mutation [ 48 ]. More importantly, these upregulated or downregulated DE genes participated in regulating viral RNA synthesis and NDV replication [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, accumulating studies have also revealed that the BRD2, BRD3 and BRD4 proteins participate in the host immune response against virus infection [ 51 53 ]. In our recent studies using quantitative proteomics analysis, we found that the parental virus rSS1GFP but not the mutant virus rSS1GFP-M/NLSm harbouring an NLS mutation in the M protein reduced the expression of the BRD2, BRD3 and BRD4 proteins to different degrees in virus-infected cells, suggesting that the decreased expression of BRD2, BRD3 and BRD4 was caused by early nuclear localization of the M protein [ 48 ]. Here, we also found that chBRD2 knockdown or overexpression continued to increase or reduce the viral titres in DF-1 cells, respectively, indicating that chBRD2 might be involved in the immune response against NDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Screening the different proteins between the normal and cancer MSCs could find key players which are responsible for cancer initiation and development ( 9 , 10 ). Spatial proteomics and TMT are the most powerful proteomics methods to identify and quantify the hallmarks of many diseases including cancer ( 57 , 58 ). Reviewing our proteomics and IPA results, we notice there are some proteins translocated abnormally into the nucleus in NSC lung cancer-MSCs compared to the normal control MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…After hypoxia−reoxygenation, TLR4/ MyD88 signaling induces TIFA interaction with TRAF6 and IRAK1, leading to rapid release of extracellular factors, such as tumor necrosis factor (TNF)-a. TIFA-mediated release of TNF-a is a predictor of survival during hemorrhage [37]. Moreover, a significant role of TIFA/TRAF6/NF-kB signaling complexes in immune surveillance was recently reported by Duan et al [38], who found that the matrix protein of a paramyxovirus, Newcastle disease virus (NDV), promotes NDV replication by reducing TIFA expression, and thus, downregulating TIFA/TRAF6/NF-kB−mediated production of cytokines [38].…”
Section: Biology Of Tifamentioning
confidence: 99%